High-Aluminum-Affinity Silica Is a Nanoparticle That Seeds Secondary Aluminosilicate Formation - Jugdaohsingh, Ravin; Brown, Andy; Dietzel, Martin; Powell, Jonathan J. (PLOS ONE, 2013)
Despite the importance and abundance of aluminosilicates throughout our natural surroundings, their formation at neutral pH is, surprisingly, a matter of considerable debate. From our experiments in dilute aluminum and silica containing solutions (pH 7) we previously identified a silica polymer with an extraordinarily high affinity for aluminium ions (high-aluminum-affinity silica polymer, HSP). Here, further characterization shows that HSP is a colloid of approximately 2.4 nm in diameter with a mean specific surface area of about 1,000 m2 g-1 and it competes effectively with transferrin for Al(III) binding. Aluminum binding to HSP strongly inhibited its decomposition whilst the reaction rate constant for the formation of the β-silicomolybdic acid complex indicated a diameter between 3.6 and 4.1 nm for these aluminum-containing nanoparticles. Similarly, high resolution microscopic analysis of the air dried aluminum-containing silica colloid solution revealed 3.9 ± 1.3 nm sized crystalline Al-rich silica nanoparticles (ASP) with an estimated Al:Si ratio of between 2 and 3 which is close to the range of secondary aluminosilicates such as imogolite. Thus the high-aluminum-affinity silica polymer is a nanoparticle that seeds early aluminosilicate formation through highly competitive binding of Al(III) ions. In niche environments, especially in vivo, this may serve as an alternative mechanism to polyhydroxy Al(III) species binding monomeric silica to form early phase, non-toxic aluminosilicates.